2023
DOI: 10.1186/s13690-023-01098-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of different regimens in the treatment of patients with latent tuberculosis infection: a systematic review and network meta-analysis of randomized controlled trials

Abstract: Background Treatment of latent tuberculosis infection (LTBI) is effective in preventing progression to TB disease. This study aimed to synthesize available evidence on the efficacy, adherence, and safety of LTBI treatment in order to assist policymakers to design appropriate national treatment policies and treatment protocols. Method The PRISMA-NMA was used to review and report this research. Randomized controlled trials which compared the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…For people who cannot take a rifamycin-based regimen because of drug intolerance, the CDC recommended treatments include: (a) six months (for HIV-negative adults and children) or nine months of daily isoniazid; (b) three months of once-weekly isoniazid plus rifapentine [ 90 ]. Short-course regimens have both higher completion rates and a lower risk of hepatotoxicity than prolonged isoniazid monotherapy [ 91 ]. It is important to note that if treatment is not taken regularly or stopped too early, the bacteria can grow again and become resistant to the drugs.…”
Section: Treatment Of Ltbi and Tb Diseasementioning
confidence: 99%
“…For people who cannot take a rifamycin-based regimen because of drug intolerance, the CDC recommended treatments include: (a) six months (for HIV-negative adults and children) or nine months of daily isoniazid; (b) three months of once-weekly isoniazid plus rifapentine [ 90 ]. Short-course regimens have both higher completion rates and a lower risk of hepatotoxicity than prolonged isoniazid monotherapy [ 91 ]. It is important to note that if treatment is not taken regularly or stopped too early, the bacteria can grow again and become resistant to the drugs.…”
Section: Treatment Of Ltbi and Tb Diseasementioning
confidence: 99%
“…In the US, most tuberculosis (TB) cases arise from the large group of approximately 13 million asymptomatic individuals with TB infection (TBI), also known as latent TBI, which can progress to active TB disease. 1 , 2 Although numerous studies have demonstrated the efficacy of TBI treatment to prevent progression to TB disease, 3 , 4 , 5 optimal TBI tests to identify individuals at risk of TB disease are needed. 6 The US Food and Drug Administration (FDA) has approved 2 test types: the tuberculin skin test (TST) and IFN-γ release assays (IGRAs), including QuantiFERON-TB Gold In-Tube (QFT-GIT; Qiagen) and T-SPOT.TB (TSPOT; Oxford Immunotec).…”
Section: Introductionmentioning
confidence: 99%
“…Preventing establishment and reactivation of LTBI is a growing priority for TB elimination strategies, although uncertainties continue to limit measurements of the relative burdens of new TB infections and LTBI reactivation [3]. Protocols that reduce the duration and adverse effects of treatment can reduce LTBI burden by improving completion rates for preventative treatment [4]. Furthermore, imperfect treatment over long periods can contribute to acquisition of drug resistance [5].…”
Section: Introductionmentioning
confidence: 99%